2021
DOI: 10.1080/21642850.2021.1938073
|View full text |Cite
|
Sign up to set email alerts
|

Using self-determination theory to predict self-management and HRQoL in moderate-to-severe COPD

Abstract: Objective: Chronic Obstructive Pulmonary Disease (COPD) is a long-term condition that detrimentally affects health-related quality of life (HRQoL), with self-management proposed as an effective treatment. Using self-determination theory (SDT), this research explored psychological need satisfaction, frustration, and behavioural regulation to explain indicators of self-management. Design and Main Outcome Measures: Cross-sectional, questionnaire-based methods in people on a pulmonary rehabilitation waiting-list. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…To explain and promote self-management in COPD patients, cognitive-behavioural theory (Williams et al, 2020), social cognitive theory (Aliakbari et al, 2020), self-determination theory (Knox et al, 2021) and Capability, Opportunity, Motivation, Behaviour (COM-B) model (Cheng et al, 2017) have been used. However, these models did not include all the knowledge, attitudes, social support and self-efficacy that are known to be related to self-management in COPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…To explain and promote self-management in COPD patients, cognitive-behavioural theory (Williams et al, 2020), social cognitive theory (Aliakbari et al, 2020), self-determination theory (Knox et al, 2021) and Capability, Opportunity, Motivation, Behaviour (COM-B) model (Cheng et al, 2017) have been used. However, these models did not include all the knowledge, attitudes, social support and self-efficacy that are known to be related to self-management in COPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…After undergoing 11 sessions over a period of 10 weeks, significant differences were observed between the intervention and control groups in terms of basic psychological needs, exercise-induced breathlessness, and functional status. Furthermore, Knox et al [24] conducted a cross-sectional survey using SDT, Health-Related Quality of Life, and self-management knowledge questionnaires on 72 moderate to severe COPD patients who had not participated in pulmonary rehabilitation. The results indicated that SDT concepts could be applied to predict controlled and autonomous regulation of self-management, self-management knowledge, and Health-Related Quality of Life in moderate to severe COPD patients who had not participated in pulmonary rehabilitation.…”
Section: Current Application Of Theoretical Models In Pulmonary Rehab...mentioning
confidence: 99%
“…Meanwhile, a mother with negative self-concept always believed that she was born unlucky with a weak physical condition, thus, she felt that for evermore, she will be poor and sick. This kind of self-perception which revolves around the belief that she is an unlucky person will also influence her mental health as well as arise a feeling of inferiority and inability to control herself from being ill continuously (Knox, Norris, Lewis, & Rahman, 2021). It is caused by the power of mind which constantly affects herself (Williams, J. M. G., & Kuyken, 2012).…”
Section: My Life As Their Mother We Won't Be Poor Forever If We Keep ...mentioning
confidence: 99%